Mathematical Analysis and Design of a Novel 5-DOF 3D Printer Robotic System - Dumlu, Ahmet; Mahboubkhah, Mehran; Ayten, Kagan Koray; Kalinay, Gurkan (Elektronika ir Elektrotechnika, 2022)
In this study, the mathematical analysis and design of a new 3D printer with 5 degrees of freedom were carried out. Thanks to the developed system, a new concept has been brought to the multi-axis 3D printer mechanisms, and thus, it is aimed to improve the part quality in additive manufacturing (AM) processes. As a result of adding the 4th and 5th axes to the moving platform of the system, the production time of the part was accelerated. It is also possible to print more complex and curved shapes with less support. To design a system with these features, first of all, the kinematic analysis of the system was obtained using vector algebra, and the workspace of the current printer was determined by considering the system constraints in this article. By giving detailed information about the mechanical and electrical components of the designed system, the working principle of the whole system is presented. According to the findings obtained in the studies, the kinematic analyses performed for the proposed system proved to be correct and a new system was proposed especially for additive manufacturing technologies.